2003
DOI: 10.1046/j.1365-313x.2003.01761.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cells of Zea mays have a complex complement of mRNAs

Abstract: SummaryAlthough double fertilization in angiosperm was discovered in 1898, we still know nothing about the proteins that mediate gamete recognition and fusion in plants. Because sperm are small and embedded within the large vegetative cell of the pollen grain, mRNAs from sperm are poorly represented in EST databases. We optimized¯uorescence-activated cell sorting (FACS) in order to isolate Zea mays sperm free of contaminating vegetative cell cytoplasm, and constructed a cDNA library. Sequencing of over 1100 cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
165
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(174 citation statements)
references
References 83 publications
(89 reference statements)
8
165
0
1
Order By: Relevance
“…We show that a sperm-specific gene, HAP2, is required for optimal ovule targeting by the pollen tube, suggesting that sperm function may impact the growth of the pollen tube. Recently, it has become clear that despite their compact chromatin structure, sperm are dynamic cells that express many genes (Engel et al, 2003;Engel et al, 2005;Xu et al, 1999); HAP2 is the first such gene with a demonstrated function in reproduction (Mori et al, 2006). It is likely that more sperm-expressed genes will be identified that play roles in pollen tube guidance and in fertilization.…”
Section: A New View Of Sperm Cells: No Longer Passive Cargomentioning
confidence: 99%
“…We show that a sperm-specific gene, HAP2, is required for optimal ovule targeting by the pollen tube, suggesting that sperm function may impact the growth of the pollen tube. Recently, it has become clear that despite their compact chromatin structure, sperm are dynamic cells that express many genes (Engel et al, 2003;Engel et al, 2005;Xu et al, 1999); HAP2 is the first such gene with a demonstrated function in reproduction (Mori et al, 2006). It is likely that more sperm-expressed genes will be identified that play roles in pollen tube guidance and in fertilization.…”
Section: A New View Of Sperm Cells: No Longer Passive Cargomentioning
confidence: 99%
“…Analyses of EST databases obtained from egg, sperm, and embryo sac EST libraries in maize (Zea mays) (Engel et al, 2003;Yang et al, 2006) indicated that several PDI-like genes were represented in these libraries. To determine if Arabidopsis homologs of these maize PDIL proteins played any role in plant reproduction, we analyzed several Arabidopsis T-DNA insertion mutants.…”
Section: Certain T-dna Insertions In Pdil2-1 Cause Reduced Seed Setmentioning
confidence: 99%
“…A cDNA library was constructed from fluorescence-activated cell sorting (FACS)-purified sperm cells of maize (Zea mays), which revealed a diverse complement of mRNAs representing at least 2,560 genes (Engel et al, 2003). These findings were significantly more than the restricted number of transcripts previously described in plant sperm cells (Xu et al, 1999a(Xu et al, , 1999bSingh et al, 2002;Okada et al, 2005).…”
mentioning
confidence: 96%
“…Additional sperm-specific genes have been reported more recently (Mori et al, 2006;von Besser et al, 2006;Ingouff et al, 2007), including DUO1, a MYB transcription factor in Arabidopsis that is important for the G2/M transition during PM II (Rotman et al, 2005). Transcriptional profiling of GCs of lily (Lilium longiflorum; Okada et al, 2006Okada et al, , 2007 revealed a considerable overlap with the maize sperm ESTs (Engel et al, 2003) and the Arabidopsis pollen microarray datasets (Becker et al, 2003;Honys and Twell, 2003). Despite this previous work, the male gamete ESTs from maize, Plumbago, and lily were limited, so that testing the potential importance of sperm-expressed transcripts by means of reverse genetics could not be comprehensive, even when an Arabidopsis homolog could be identified for such ESTs.…”
mentioning
confidence: 99%